2021
DOI: 10.1002/adhm.202100907
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐Confined Tumor‐Docking Reversible Thermogel Potentiates Systemic Antitumor Immune Response During Near‐Infrared Photothermal Ablation in Triple‐Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) features immunologically "cold" tumor microenvironments with limited cytotoxic T lymphocyte (CTL) infiltration. Although ablation therapies have demonstrated modulation of "cold" TNBC tumors to inflamed "hot" tumors, recruitment of myeloid derived suppressor cells (MDSCs) at the tumors post ablation therapies prevents the infiltration of CTLs and challenge the antitumor potentials of T-cell therapies. Here, a thermal ablation immunotherapy strategy is developed to prevent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…Previously, we demonstrated that R848 can significantly reduce the MDSC population in primary and secondary 4T1 breast cancer tumors. 17 In the present study, MDSCs were significantly reduced in the primary (Fig. S15B and S18†) and secondary tumors (Fig.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Previously, we demonstrated that R848 can significantly reduce the MDSC population in primary and secondary 4T1 breast cancer tumors. 17 In the present study, MDSCs were significantly reduced in the primary (Fig. S15B and S18†) and secondary tumors (Fig.…”
Section: Resultssupporting
confidence: 57%
“…14 Recent studies have demonstrated that R848 can modulate the tumor microenvironment by inducing macrophage repolarization and enhancing dendritic cell maturation to activate cytotoxic T lymphocytes and induce anti-tumor activity. 15–18 Rodell et al have shown that crosslinked beta cyclodextrin loaded R848 nanoparticles can enhance antitumor immunity by polarizing TAMs to M1 inflammatory macrophages. 19 Previously, we demonstrated that R848 administration in triple-negative breast cancer can reduce myeloid-derived suppressor cells (MDSCs) and enhance CD8+ T cell populations in primary and secondary tumors during photothermal therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, photonic hyperthermal-assisted immunotherapy could perform immunoadjuvant-like effects to mobilize tumor-attacking immunity [ 194 , 195 ]. The common photothermal immunomodifiers consist of Au-derived nanomaterials, near-infrared (NIR) dye small molecules and others [ 196 , 197 ].…”
Section: Modern Immunotherapeutic Strategies Based On 3d Macroscale B...mentioning
confidence: 99%
“…Nanoparticle-mediated photothermal therapy (PTT) has emerged in recent years for local tumor ablation, tumor growth arrest, and activating antitumor immune responses. , The use of organic compounds and nanoparticles in near-infrared (NIR) laser-irradiated PTT is an effective therapeutic strategy for antitumor therapy. The application of PTT-mediated thermal ablation to tumor tissues at mild temperatures induces immunogenic cell death (ICD), which releases danger-associated molecular patterns (DAMPs). For example, calreticulin expression in cancer cells alters antitumor immune responses via antigen presentation. However, the therapeutic results are limited because of the inability of light to effectively penetrate large tumors as well as inadequate thermal ablation, both of which cause tumor relapse and regrowth.…”
Section: Introductionmentioning
confidence: 99%